Barbara Pym: The Apology of Singleness - Чернокова, Евгения Семеновна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The paper focuses on semantics and poetics of Barbara Pym’s (1913-1980) novels in the context of the English-American criticism tradition of comparing her to Jane Austen. In “A Few Green Leaves” (1979) the “novel of manners” traditions and the nature of narrative plot are being reconsidered. The paper states  the solitude of her heroes  not as marginality, or  destiny, or existential “mastering” but as an identity, conscious choice and humanistic assumption.